Short-term effects of triiodothyronine on thyroid hormone receptor alpha by PI3K pathway in adipocytes, 3T3-L1 - Oliveira, Miriane de [UNESP]; Castro Olimpio, Regiane Marques [UNESP]; Sibio, Maria Teresa de [UNESP]; Fontes Moretto, Fernanda Cristina [UNESP]; Mello Luvizotto, Renata de Azevedo; Nogueira, Celia Regina [UNESP] (Sbem-soc Brasil Endocrinologia &metabologia, 2014)
Objective: The present study aimed to examine the effects of thyroid hormone (TH), more precisely triiodothyronine (T3), on the modulation of TH receptor alpha (TR proportional to) mRNA expression and the involvement of the phosphatidyl inositol 3 kinase (PI3K) signaling pathway in adipocytes, 3T3-L1, cell culture. Materials and methods: It was examined the involvement of PI3K pathway in mediating T3 effects by treating 3T3-L1 adipocytes with physiological (P = 10nM) or supraphysiological (SI = 100 nM) T3 doses during one hour (short time), in the absence or the presence of PI3K inhibitor (LY294002). The absence of any treatment was considered the control group (C). RT-qPCR was used for mRNA expression analyzes. For data analyzes ANOVA complemented with Tukey's test was used at 5% significance level. Results: T3 increased TR proportional to mRNA expression in P (1.91 +/- 0.13, p < 0.001), SI (2.14 +/- 0.44, p < 0.001) compared to C group (1 +/- 0.08). This increase was completely abrogated by LY294002 in P (0.53 +/- 0.03, p < 0.001) and SI (0.31 +/- 0.03, p < 0.001). To examine whether TRa is directly induced by T3, we used the translation inhibitor cycloheximide (CHX). The presence of CHX completely abrogated levels TRa mRNA in P (1.15 +/- 0.05, p > 0.001) and SI (0.99 +/- 0.15, p > 0.001), induced by T3. Conclusion: These results demonstrate that the activation of the PI3K signaling pathway has a role in T3-mediated indirect TRa gene expression in 3T3-L1 adipocytes.
Keywords: Triiodothyronine; Adipocytes; TR alpha; PI3K